DISTRIBUTIONAL PATTERNS OF THE NEOTROPICAL AND ANDEAN SPECIES OF THE GENUS BOMBUS (HYMENOPTERA: APIDAE) - Abrahamovich, Alberto H.; Díaz, Norma B.; Morrone, Juan J. (Instituto de Ecología, A.C., 2004)
Distributional patterns of the Neotropical and Andean species of the genus Bombus Latreille were analyzed, by comparing individual tracks of 36 species. Eight generalized tracks were found: (1) Mexican Mountain (B. [Fv.] fervidus [Fabricius], B. [Br.] haueri Handlirsch, B. [Pr.] hunti Greene, and B. [Cu.] rufocinctus Cresson); (2) Northern Mesoamerican (B. [Br.] brachycephalus Handlirsch, B. [Fv.] diligens Smith, B. [Ds.] macgregori Labougle & Ayala, and B. [Fv.] steindachneri Handlirsch); (3) Southern Mesoamerican (B. [Fv.] digressus [Milliron] and B. [Ps.] variabilis [Cresson]); (4) Widespread Mesoamerican (B. [Pr.] ephippiatus Say, B. [Fv.] medius Cresson, B. [Fv.] mexicanus Cresson, B. [Fv.] pennsylvanicus [DeGeer], and B. [Fv.] weisi Friese); (5) Northern Andean (B. [Cc.] coccineus Friese, B. [Rb.] ecuadorius Meunier, B. [Fv.] excellens Smith, B. [Fr.] funebris Smith, B. [Ds.] handlirschi Friese, B. [Rb.] hortulanus Friese, B. [Rb.] melaleucus Handlirsch, B. [Fv.] pullatus Franklin, B. [Rb.] robustus Friese, B. [Fr.] rohweri Frison, and B. [Rc.] rubicundus Smith); (6) Yungas (B. [Cc.] baeri Vachal and B. [Rb.] tucumanus Vachal); (7) Southern Brazilian (B. [Fv.] bellicosus Smith and B. [Fv.] brasiliensis Lepeletier) and (8) Widespread South American (B. [Fv.] atratus Franklin, B. [Fv.] morio [Swederus], B. [Fv.] opifex Smith, and B. [Fv.] transversalis [Olivier]). Three panbiogeographic nodes were determined: (A) Isthmus of Tehuantepec, in the intersection of the Northern and Southern Mesoamerican generalized tracks; (B) Panama, in the intersection of the Southern Mesoamerican and Northern Andean generalized tracks, and (C) Puna, in the intersection of the Northern Andean and Yungas generalized tracks. These patterns reflect the complex biogeographic history of the Neotropical and Andean regions.